Tendering and estimating process in construction company - Syazwan Fikri Bin Elyas (School of Environmental Engineering, University Malaysia Perlis, 2014)
The objective of this study is to study the tendering and estimating process in the contractors company, to identify the factor that influence the contractors profit margin and to examine the tendering strategy by the contractor to successfully win the bid. The study involved G7 companies registered with the CIDB around Perlis, Kedah and Penang. The analysis was performed with questionnaires and interviews.